PERAN KPU KOTA SEMARANG DALAM MENINGKATKAN PARTISIPASI POLITIK MASYARAKAT PADA PEMILIHAN GUBERNUR JAWA TENGAH TAHUN 2018 - Mulya Rahman; Muhammad Adnan (Journal of Politic and Government Studies, 2019)
In the electoral processes, such as legislative, president, and governor election, KPU in the province as well as city has important role. KPU is a institution of election organizer that is national, permanent, independent. KPU must free from the influence of any party relating to the implementation of its duties and authorities. Society participation becomes very important in the success of election. One of the main factors that makes election success or not is how society participation in using their right to vote. In this study, the researcher want to know what KPU has done in increasing society political participation in Semarang with using descriptive qualitative method. This study is conducted in Semarang, Central Java with using data collecting method, such as interview and document. The findings of this study are Semarang’s KPU has carried out its role in increasing society political participation through direct and indirect socialization to all society, the success of Semarang’s KPU in increasing society participation, and well cooperation between institutions in increasing society social participation. It is expected that the role of Semarang’s KPU in increasing society political participation in the next election will be even better. Keyword: Role, Participation, Socialization, Election, Level of Participation, Election